Combinatorial synthesis and high‐throughput characterization of the thin film materials system Co–Mn–Ge: Composition, structure, and magnetic properties. Issue 9 (17th April 2015) - Salomon, Steffen; Hamann, Sven; Decker, Peer; Savan, Alan; Meshi, Louisa; Ludwig, Alfred
Abstract : Co–Mn–Ge is a system of interest for magnetocaloric applications as a solid state magnetic refrigerant. A thin film materials library covering a large fraction of the Co–Mn–Ge ternary composition space was fabricated by sputter deposition. After deposition, it was annealed at 600 °C for 3 h and quenched subsequently. An energy‐dispersive X‐ray spectroscopy and X‐ray diffraction‐based cluster analysis revealed the regions of existence for the CoMnGe and the Co2 MnGe single phase areas. Furthermore, high intensity diffraction peaks revealed the presence of the hexagonal (Co, Mn)7 Ge6 phase in a region that also featured the CoMnGe phase. In this region, a non‐linear, symmetric, and hysteretic shift of the (200) diffraction peak of the (Co, Mn)7 Ge6 phase was observed by temperature‐dependent X‐ray diffraction for Co23 Mn33 Ge44, indicating a structural phase transition taking place between 350 and 375 K upon heating and 325 and 300 K upon cooling. This coincides with a magnetic transition near 325 K from the ferromagnetic to the paramagnetic state. However, no magnetostructural coupling was identified in the temperature range from 330 to 300 K upon cooling. Magnetostriction and an undetected structural transition of the CoMnGe phase were ruled out as probable causes for the non‐linear shifts.